2021
DOI: 10.21037/tcr-21-1047
|View full text |Cite
|
Sign up to set email alerts
|

Lidocaine inhibits the proliferation and metastasis of epithelial ovarian cancer through the Wnt/β-catenin pathway

Abstract: Background: Lidocaine, an amide local anesthetic, has recently been found to have anticancer action in various cancer cells. However, the role of lidocaine in epithelial ovarian cancer (EOC) remains largely unknown. In the present study, we investigated how lidocaine regulates the progression of EOC.Methods: Real-time polymerase chain reaction was used to examine the expression of Snail, Wnt, β-catenin, E-cadherin, vimentin, matrix metalloproteinase (MMP)-7, MMP-9, and vascular endothelial growth factor in lid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“… 17–19 Lidocaine was also found to inhibit the WNT/beta-catenin pathway, thus blocking epithelial-mesenchymal transition and impairing the progression of ovarian cancer. 20 Bupivacaine reportedly interferes with gastric cell migration by blocking the RHO-A/RHO-associated protein kinase (ROCK)/myosin light chain (MLC) pathway, and ropivacaine reduces the migration of esophageal and thyroid cancer cells by inhibiting the RAS-related C3 botulinum toxin substrate 1/c-JUN N-terminal kinase/paxillin/focal adhesion kinase (RAC1/JNK/paxillin/FAK) pathway and integrin-alpha-2 expression, respectively. 21–23 Moreover, ropivacaine may interact with integrin-beta1, which is involved in tumorigenesis, ultimately inducing apoptosis.…”
Section: Preclinical Investigationmentioning
confidence: 99%
“… 17–19 Lidocaine was also found to inhibit the WNT/beta-catenin pathway, thus blocking epithelial-mesenchymal transition and impairing the progression of ovarian cancer. 20 Bupivacaine reportedly interferes with gastric cell migration by blocking the RHO-A/RHO-associated protein kinase (ROCK)/myosin light chain (MLC) pathway, and ropivacaine reduces the migration of esophageal and thyroid cancer cells by inhibiting the RAS-related C3 botulinum toxin substrate 1/c-JUN N-terminal kinase/paxillin/focal adhesion kinase (RAC1/JNK/paxillin/FAK) pathway and integrin-alpha-2 expression, respectively. 21–23 Moreover, ropivacaine may interact with integrin-beta1, which is involved in tumorigenesis, ultimately inducing apoptosis.…”
Section: Preclinical Investigationmentioning
confidence: 99%
“…This in vitro study suggests that bupivacaine may possess a direct anti-cancer effect by activating apoptotic pathways against ovarian and prostate cancer. Sun et al have also reported that the inhibitory effects of lidocaine on cell proliferation and metastasis are mediated by the Wnt/β-catenin pathway of ovarian cancer cells [ 72 ]. Similar results are also found in HCC, where lidocaine treatment causes apoptosis through the activation of pro-apoptotic protein Bax, caspase cascade, and a corresponding decrease in anti-apoptotic protein Bcl-2 through the extracellular signal-regulated kinase (ERK) 1/2 and p38 pathways.…”
Section: Repurposing Anesthetic/sedative Drugs Into Anticancer Treatmentmentioning
confidence: 99%
“…β‐Catenin is a key protein that promotes the development of human cancer. For example, β‐catenin downregulation could contribute to cisplatin‐based chemotherapy for bladder cancer, 3 and its inhibition could contribute to the suppression of proliferation and metastasis of ovarian cancer cells 4 . β‐Catenin is not only a component of the Wnt/Wg pathway 5 but also promotes cell adhesion 6 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, β-catenin downregulation could contribute to cisplatin-based chemotherapy for bladder cancer, 3 and its inhibition could contribute to the suppression of proliferation and metastasis of ovarian cancer cells. 4 β-Catenin is not only a component of the Wnt/Wg pathway 5 but also promotes cell adhesion. 6 Similarly, the Wnt/β-catenin pathway plays an important role in CRC development.…”
Section: Introductionmentioning
confidence: 99%